Zarządzanie wiedzą a efekty synergii w obszarze logistyki organizacji wielopodmiotowych (wyniki badań) - Pastuszak, Zbigniew; Chadam, Jan (Knowledge Management and a Synergy in Logistics of Multi-Entity Enterprises (The Results of the Research), 2005)
The goals of setting up and running enterprises are commonly known. However, can the influence of multi-entity enterprises be brought down to the sheer sum of their accomplishments? What is the added value of multi-entity companies for themselves and their customers? What is the role of knowledge management in the process of its generation? This article presents the results of a research conducted on Polish capital groups. It included an analysis of the selected aspects of knowledge management and an attempt to identify the influence of knowledge on synergy processes in logistics and organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 372-380